Perubahan Sosial Sistem Kekerabatan dalam Upacara Adat Perkawinan Masyarakat Nias (Studi Kasus Tahapan Fanika Era-Era Mbowo) di Desa Tuhembuasi Kecamatan Sogae’adu Kabupaten Nias - Fatizaro Gulo; Masniar H. Sitorus; Harisan Boni Firmando; Ade Putera Arif Panjaitan; Martua Sihaloho (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
The title of this research emphasizes social changes in the kinship system in the traditional marriage ceremony of the Nias community (case study of the fanika stages of the mbowo era) in Tuhembuasi Village, Sogae'adu District, Nias Regency. The aim of this research is: To find out/describe social changes in the kinship system in the traditional marriage ceremony of the Nias community (case study of the fanika stages of the mbowo era) in Tuhembuasi Village, Sogae'adu District, Nias Regency. In this research, the method used is a descriptive qualitative approach. The results of the research show that the causes of changes in the Fanika stages of the Mbowo era in the Nias tribe community in Tuhembuasi Village, Sogae'adu District, Nias Regency are: (1) parents nowadays are very busy so they don't have time to talk about or teach about customs. and the culture of the Nias people to their children; (2) because the implementation of the Fanika stages in the Mbowo era took a lot of time, up to 3 to 4 hours, so people also felt bored because the time was too long, so the implementation of this stage was often postponed; (3) many people currently have very little experience of Nias culture so that the implementation of its customs as they are is important to remember but is not implemented; (4) migrate, marry with other tribes, so that the celebration does not reflect Nias culture.